Temperature modulation alters the gut and skin microbial profiles of chum salmon (Oncorhynchus keta) - Ghosh, Subrata Kumar; Wong, Marty Kwok-Shing; Hyodo, Susumu; Goto, Shuji; Hamasaki, Koji (Frontiers in Marine Science, 2022)
Fish-associated microbiota are an integral part to the health of the host fish. The ongoing climate changes including global warming of water may disrupt the composition and diversity of host-microbiota, and subsequently, destabilize the fish homeostasis. Since the knowledge on temperature-sensitive marine fish and environmental bacteria is scarce, we investigated the effects of rearing temperatures on community structure, diversity and assembly process of bacteria on chum salmon (Oncorhynchus keta), which is a temperate salmon species found in the Pacific. Over the course of two weeks, laboratory-raised chum salmon were exposed to three temperatures: high (18 °C), low (8 °C) and, control (13 °C). Their feces, cutaneous mucus, and surrounding water were sampled for community structure analysis based on 16S rRNA gene amplicon sequencing. Temperature changes from the control level triggered significant dysbiosis in the fecal and skin mucus microbiota. In particular, Vibrio and Tenacibaculum sequence variants were highly abundant at high and low temperatures, respectively, and the opportunistic growth of these pathogenic species may impede host immunity. Two temperature-specific taxonomic microbial biomarkers, the class Betaproteobacteria and the genus Flavobacterium were identified at both high and low temperatures. An analysis of bacterial community assembly processes revealed that environmental selection significantly affected the gut microbial community assembly, while the assembly process of the skin microbiota was stochastic. Our study elucidated the potential crisis of fish health when the equilibrium of the cutaneous and intestinal microbiota was disrupted by temperature changes. Our data will be a valuable tool to better understand the effects of climate change, a very pressing and important challenge now and in the future, on the fish microbiota and its homeostasis.